النظرية التفاعلية في تعلم اللغة الثانية والاستفادة منها في تعليم اللغة العربية للناطقين بغيرها - Saufa Mujadilah (Rayah Al-Islam, 2019)
This research uses descriptive analytical approach based on the analysis of reality, relying on documents and scientific method to get information in the analytical view of interactive theory in the second language learning using the tool research and analysis of the content. The results of this research showed that the interactive theory of learning a second language had the relationship between behaviorism approach and the approach of nativism in the sense of interaction between mental ability learners and the surrounding environment. In another sense, although students have the ability to think to learn a second language, but she needs a surrounding environment, due to the interaction of these two elements that will support the learning of a second language. As for the application of this theory in teaching Arabic to non Arabic speakers depending on the following principles: the interaction between teachers and students, the interaction between the student and the student, the interaction between the learner and the environment, interaction between students and the community, interaction between the learner and culture, then lean on collaborative learning, and depending on the cause, application and reinforcement.